Green industrial performance: the GIP index. (2018) - Alba, Jaime Moll De; Todorov, Valentin
This article develops and introduces the green industrial performance (GIP) index that allows policy-makers and practitioners to analyse the performance of countries in terms of green manufacturing. We derive our data from international data sources, namely UNIDO's industrial statistics database (INDSTAT) and UN COMTRADE, to build up a set of green industrial indicators capturing different aspects of the country's green industrial performance. We then construct a composite index and rank and analyse the green industrial performance of a set of 107 countries in 2014. In 2014, the top five green industrial performers according to the GIP index are Denmark, Taiwan Province of China, Germany, the Republic of Korea and Singapore. Industrialised economies generally outperform other economies. We derive from the GIP index a set of recommendations for future research within the general framework of the international 2030 Sustainable Development Agenda.